Seed yield and nutrition in slow-wilting soybean breeding lines as influenced by irrigated and non-irrigated conditions in the Midsouth USA - Bellaloui, Nacer; Smith, James R.; Mengistu, Alemu; Abbas, Hamed K. (Frontiers in Plant Science, 2026)
Soybean seed is an important source of protein, oil, and sugars. Soymeal quality is determined by protein and oil contents and sugar profile. Drought results in yield loss and poor seed quality, affecting seed nutrition, including protein, oil, and sugars. Therefore, identifying breeding lines tolerant to drought and investigating possible drought response mechanisms for these lines are important. The objective of this research was to investigate the response of seed yield and seed composition of slow-wilting soybean breeding lines under irrigated and non-irrigated conditions. A 3-year experiment was conducted in Stoneville, MS, USA, in 2015, 2016, and 2018 using slow-wilting (SW) (drought tolerant) trait breeding lines (N98–7265 and PI 471938) of maturity group (MG) V. The checks were 5601T (standard public variety), A5959 (fast-wilting, FW, commercial variety), and Hutcheson (FW parent). The results showed that under irrigated conditions, seed protein was lower and oil was higher in SW genotypes compared with those of checks. No consistent pattern was shown for oleic and linolenic acids under irrigation conditions. Under non-irrigated conditions, seed protein and oleic acid were higher in SW genotypes than checks. Oil content was inconsistent in SW across years. Seed yield was lower in SW genotypes under irrigated and non-irrigated in all 3 years. One possible response mechanism of SW trait is that SW soybean has the ability to maintain leaf water potential and conserve water to use it during drought period. This is reflected by the fact that SW genotypes maintained leaf water potential (LWP) at about -1.20 Ψw under non-irrigated conditions compared with those of checks (about -2.77 Ψw). Moreover, SW genotypes may use high seed sugar (stachyose) accumulation as a response mechanism under non-irrigated conditions to protect seed from damage. The lower yield of SW genotypes cannot be explained by LWP due to their consistent lower yield in all 3 years. This research helps to understand the mechanisms of drought tolerance and helps breeders to select varieties for high seed nutritional qualities such as higher desirable sucrose and lower undesirable raffinose and stachyose under the harsh conditions of high heat and drought of midsouth US.